Influence of psychological capital and person-environment fit on job attitudes and turnover intention among China 5-star hotels’ frontline employees - Yan, Zhen (2020)
The hospitality industry has always been a great generator of global GDP and employment. However, high rates of turnover have gradually undermined this industry and brought huge losses. This has brought attention for this study to identify factors that affect turnover intention especially among the frontline employees in China’s international 5-star hotels. The purpose is to examine the intangible determinants of individual factors which include the psychological capital and person-environment fit in influencing the frontline employees’ turnover intention. Data were collected among frontline employees from front office, food and beverage, housekeeping and marketing departments in international 5-star hotels in Guangzhou, Hangzhou, Chengdu, Qingdao and Xi’an. A quantitative method was adopted and a structured self-administered questionnaire was utilized. A total of 616 usable questionnaires were obtained from frontline employees through purposive sampling technique. Data was analyzed using the Structural Equation Modeling (SEM) technique via IBM SPSS Statistics (version 23.0) and IBM SPSS AMOS (version 23.0). The path analyses revealed that both psychological capital and person-environment fit had negative influence on turnover intention. In addition, job satisfaction, organisational commitment and job involvement were all positively influenced by person-environment fit. However, psychological capital only significantly affected job satisfaction and organisational commitment but not job involvement. Next, these three job attitudes were significant predictors of turnover intention. As for the mediating effects, job satisfaction and organisational commitment mediated the relationship between psychological capital and turnover intention. On the other hand, the above-mentioned three job attitudes had significant mediating effects on the relationship between person-environment fit and turnover intention. Finally, this study confirms that conservation of resources (COR) theory can provide a sound theoretical underpinning of the adoption of individual psychological determinants reducing turnover intention in the hotel sector. In a similar vein, this study affirms that Steers and Mowday’s (1981) model of turnover is quite useful in providing new dimensions of job attitudes as mediators and also this classic turnover model can explain the relationship between job attitudes and turnover intention well. To conclude, this study provides insights for effective retention strategies from psychological perspective to mitigate the turnover issue among frontline employees in international 5-star hotels in China.